Premature Birth and Association with Maternal Perception of Insufficient Social Support in a Sample of Iraqi Women - Dr. Entidhar Nasir Frak; Dr. Hala Hussein Jasim (Academic Journal of Clinicians, 2024)
Background: Preterm delivery is acknowledged in the literature as a distressing and traumatic occurrence for parents and their newborn child due to potential difficulties throughout pregnancy. Objective: To assess whether there are differences in the perception of SS measured MOS scale between women who have preterm birth and those who they have full-term labor. Patients and methods: Study of case controls conducted in 3 hospital (1 public hospital+2 private hospital) in Baghdad city at the period between the first of January 2022 to the 31 of Dec 2022. Results: The maternal-fetal health variables that had association with obesity at childbirth (OR 0.4, 95% CI 0.17-0.60, and P<0.001), insufficient prenatal control (OR CI 2.76-8.80), maternal pathology of the pregnancy (OR 3.98, 95% CI 2.31-7.30, and P<0.001) and pathology fetal (OR 7.39; 95% CI 3.32-16.79, and P<0.001). The psychological variables showed no association. The dimension positive social interaction insufficient maintained association with prematurity (OR 1.93, 95% CI 1.18-3.63, and P=0.04( Among the association between prematurity and social support (SS) was higher in maternalfetal health (OR=1.76, 0.97-3,12, and P=0.6). Conclusion: There was no statistically significant variation in the average MOS score. The dimension of the MOS survey that was linked to prematurity is positive social contact. Validation of the MOS scale for use during pregnancy is necessary, or alternatively, a new measurement scale specifically designed for this purpose should be developed.